Estudo da interação entre camadas de super-redes supercondutor/isolante/ferromagneto - Yonamine, Anne Hitomi [UNESP] (2014)
The superconducting (SC) YBa2Cu3O7 (YBCO) was discovered in 1986, and since than it has been widely studied in its various forms and properties. Among its many features, its high critical temperature is one of the most important in science and technology fields. Currently there are several devices based on YBCO. The SC/FM heterostructures, where FM is a ferromagnetic layer, created in recent decades, is one of the most interesting ways of applying this material. These are highly promising for the development of spintronic devices exploding the properties of electron spins. In this work the focus was to study the effects of interactions between the YBCO layer and the ferromagnet La2/3Ca1/3MnO3 in superlattices mediated by layers of differente thicknesses of certain insulating materials. The tested insulating material were SrTiO3 (STO), CeO2 and PrBa2Cu3O6. The superlattices were fabricated by PLD technique with optimized parameters. Some of the features were determined by measurements of XRD, SEM, EDS, magnetization and electric transport. Structurally, the superlattices showed integrity of composition and crystallinity with preferencial growth in the c-direction. The SEM images confirmed the epitaxial growth of the layers, and the EDS confirmed the composition. The magnetization measurements showed the quality and behavior of the superlattices which results from the interaction or uncoupling of SC and FM layers when an insulating layer is inserted between them. The same analysis was done in transport measurements. The superlattices (YBCO20mn/ISOdl/LCMO10mn)x20 showed predominantly superconducting behavior. While (YBCO20nm/ISOdl?LCMO20mn)x20 superlattices showed oscillations on critical and Curie temperatures as well as unusual magnetization and resistivity which depended on the insulation and its thickness. The STO acted as an efficient insulator between the SC and FM layers, resulting in superlattices modulated by the superconducting...